Out-patient intravaginal misoprostol versus in-patient intravaginal misoprostol for the treatment of first trimester incomplete miscarriage in UKMMC: a randomised controlled trial. - Annamalai,; Lim, Pei Shan; Nur Azurah AG,; Aqmar Suraya Sulaiman,; Syed Zulkifli Syed Zakaria,; uhammad Abdul Jamil Mohd. Yassin, M (Department of Surgery, UKM Medical Centre, 2014)
A prospective randomised controlled trial was conducted at a tertiary medical center on 154 patients for the treatment of spontaneous first trimester incomplete miscarriage. The intervention group (n=77) received out-patient administration of misoprostol whereas the control group (n=77) received in-patient administration of misoprostol. The intravaginal misoprostol dosage administered was 800mcg 8 hourly to maximum of 3 doses. They were reassessed at Day 7. The primary outcome evaluated were success of evacuation, side effects, cost and patient acceptability. The secondary outcomes evaluated were mean reduction of endometrial thickness, days of passing out POC, duration of bleeding and mean reduction in hemoglobin. Assessment for treatment failure was done at day 7. Surgical evacuation was then offered.